PLOT ANALYSIS IN THE GIVER NOVEL BY LOIS LOWRY - Anggriani, Ni Putu; Candra, Komang Dian Puspita; Juniartha, I Wayan (LITERA : Jurnal Bahasa Dan Sastra, 2022)
ABSTRACTPlot is the literary term that describes the element of a story. This research concerns toanalyze about plot elements in the novel entitledâ€œThe Giverâ€ by Lois Lowry. Observationmethod are used in collecting the data by following several steps those are by finding thekeyword belongs to each elements of plot, reading repeatedly, understanding the storywhile taking note. In this study, the data were analyzed descriptive qualitatively by usingthe theory from Freytag as cited in Macewan (1900). The finding of this research showthat this novel applied dramatic plot which are consists of several elements namely risingmovement, climax, falling action, and resolution. Exposition is talking about Jonas whoare in eleven years old and become twelve in December live in community with hisparents and little sister, but they all do not have blood relation because all children bornfrom biological mother. He was frightened, but he decided not frightened but toapprehensive to happening in December. Rising movement happened when Jonas haveasiggment from Chief Elder to become a receiver of memory, climax happened whenJonas realizes his father â€œreleasesâ€ the newchildren actually that Kill. Falling actionhappened when Jonas escape from Community to take Gabriel in order to save Gabrielfrom being â€œReleaseâ€ and the last catastrophe or resolution happened Jonas and gabrielride to another place he sees distance light and hear people singing.Keyword: plot, plot type, The Giver novelABSTRAKAlur adalah istilah sastra yang menggambarkan unsur cerita. Penelitian ini bertujuanuntuk menganalisis elemen yang menyusun alur cerita dalam novel Lois Lowry â€œTheGiverâ€. Peneliti ini menggunakan metode observasi dalam pengumpulan data denganmenerapkan langkah-langkah yaitu mencari kata kunci yang menunjukkan bagian darielemen-elemen, membaca berkali-kali, memahami cerita, dan mencatat. Penelitian inidianalisis secara deskriptif kualitatif menggunakan teori dari Freytag yang dikutip dariMacewan (1900). Jenis plot yang diterapkan dalam novel adalah plot dramatis yangterdiri dari beberapa elemen yaitu cerita permulaan, penanjakan, klimaks, keteganganmenurun, dan peleraian. Permulaan diawali dengan memperkenalkan karakter ceritaketika Jonas berusia sebelas tahun yang menjadi dua belas bulan desember tinggal diKomunitas bersama orang tua dan adik perempuannya, yang mereka tidak memilikihubungan darah karena semua anak lahir dari ibu kandung. Ia takut, dan ia berusahatidak takut tapi bersemangat untuk menunggu apa yang terjadi dibulan desember. Ceritapenanjakan terjadi saat Jonas mendapat penugasan dari Chief Elder menjadi penerimamemory, klimaksnya terjadi saat Jonas menyadari ayahnya â€œmelepaskanâ€ anak-anakbaru itu sebenarnya membunuh. Ketegangan menurun terjadi saat Jonas melarikan diridari Komunitas untuk mengambil Gabriel untuk menyelamatkan Gabriel dari "Lepaskan dan pertikaian atau peleraian terjadi ketika Jonas dan Gabriel naik ke tempat lain, Iamelihat cahaya dikejauhan dan mendengar orang bernyanyi.Kata Kunci: alur, jenis alur, novel The Giver